Industrial activity and changes in its spatial structure in Poland during the SARS-CoV-2 pandemic - Brezdeń, Paweł (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2022)
The article deals with the issue of the assessment of industrial activity during the SARS-CoV-2 pandemic in Poland by voivodeship. The aim of the study is to identify the scale of the impact of the SARS-CoV-2 pandemic period in the years 2020-2021 on industrial activity and to determine the consequences in the spatial structure of industry in the system of voivodeships in Poland. The scope of issues adopted for analysis depended on the availability of data, especially at the regional level. The study presents analyses of the basic features characterising industrial activity, i.e. the value of industrial production, the number of employees, the number of entities registered in industrial activity, or the value of the general economic climate indicator in manufacturing. The analyses of the regional structure of industry were complemented by the survey of the survival rate of entities, measured by the number of entities undertaking activities in industry and the number of entities deregistered in the quarters of the analysed period. The results of the conducted research indicate a clear effect of the impact of the first wave of COVID-19 cases (Q2 2020) on the basic parameters of industrial activity. During the pandemic period (Q4 2019 and Q2 2021), the spatial structure of industry in Poland was characterised by high stability, it changed only by less than 3%. Despite high stability, the spatial structure of industrial production was, however, subject to certain fluctuations. The largest changes in the spatial structure of industrial production took place between Q2 2020 and Q2 2019 - 4%. The essential feature of the ongoing structural changes is the relative reduction of disproportions between the distribution of industrial production to individual Polish voivodeships.